THE INFLUENCE OF SELF-EFFICACY AND PEER SUPPORT ON ACADEMIC PROCRASTINATION IN WRITING A THESIS - Pawestri, Allycia Trecy; Moesarofah, Moesarofah (LP2M IAI Al-Khairat Pamekasan, 2024)
This research aims to determine the effect of self-efficacy and peer support on academic procrastination in preparing a thesis for batch 2020 FPP students at PGRI Adi Buana University Surabaya. This type of research is quantitative. The sample used simple random sampling and amounted to 104 students. The data collection method in this study used a measurement scale. The data analysis technique uses multiple linear regression analysis, which aims to predict the effect between variables, including the t-test, f-test, and R2. The result showed that (1) self-efficacy has a negative and significant effect on academic procrastination in preparing a thesis, which is -0.726 and 0,000<0,05. (2) peer support has a negative and significant effect on academic procrastination in preparing a thesis, which is -0.156 and 0,019<0,05. (3) self-efficacy and peer support have simultaneous and significant effects on academic procrastination in preparing a thesis, which is 72,164 and 0,000<0,05.